5, 10-methylenetetrahydrofolate reductase C677T gene polymorphism and peripheral arterial disease: A meta-analysis. (December 2021) - Liu, Fanyun; Du, Jun; Nie, Menglin; Fu, Jian; Sun, Jianming
Introduction: Peripheral arterial disease is one common vascular disease most caused by atherosclerosis. As with stroke and coronary heart disease, peripheral arterial disease is one clinical type of atherosclerotic cardiovascular disease with many unmeasured environmental and genetic components. MTHFR C677T polymorphism is associated with the increased risk of ischemic stroke and coronary heart disease. MTHFR C677T polymorphism is associated with decreasing enzyme activity and increasing homocysteine levels. Meta-analysis of studies had demonstrated an association between elevated plasma homocysteine levels and peripheral arterial disease. Elevated plasma homocysteine level is closely related to MTHFR C677T polymorphism. Recent studies had clarified the relationship of MTHFR C677T polymorphism and peripheral arterial disease. So we performed a meta-analysis to investigate the association between MTHFR C677T polymorphism and peripheral arterial disease. Materials and methods: We searched the database PubMed, Embase, and Cochrane Library for all English-language articles related to peripheral arterial disease and MTHFR C677T through 30 June 2020. Analysis results were shown by forest plot. Publication bias was estimated using funnel plot. Results: A total of 15 studies comprising 1929 patients with peripheral arterial disease and 2952 healthy controls were included in the meta-analysis. Significant associations between MTHFR C677T genetic polymorphism and peripheral arterial disease were found (OR = 1.31, 95% CI: 1.09–1.58, P <0.01). But there was no significant association (poor OR = 1.11, 95% CI: 0.98–1.26, P =0.11) between the T allele carrier and peripheral arterial disease. Conclusion: Our meta-analysis suggested that MTHFR C677T genetic polymorphism TT genotype may be associated with increased peripheral arterial disease risk. But further studies with large sample sizes are needed to confirm our findings.